An Analytical Review of Projects in the Energy Development Field Dugda I Coal Washery Bisrampur Coal Mine Chandrapura Thermal Power Station - Planning Commission, Government of India (Planning Commission, Government of India, 1965)
As part of its continuing studies of management practices in the public sector, the Committee on Plan Projects (COPP) initiated a series of analytical reviews in the energy development field. These reviews are part of the management programme of study undertaken by COPP to institute improved planning and control methods; used within Public Sector projects.
Management Group Committee on Plan Projects, Planning Commission
Management group Committee on Plan Project, Planning Commission, Government of India
Keywords: Coal industry; Economic aspects; Production and Development of coal